2020
DOI: 10.1002/hrm.22008
|View full text |Cite
|
Sign up to set email alerts
|

Recessionary actions and absence: A workplace‐level study

Abstract: Actions such as work restructuring and wage and employment freezes taken by organizations in response to recessions are widely assumed to decrease employees' job security and detrimentally affect perceptions of management's trustworthiness. We assess whether these effects occur and if, in turn, they affect workplace absenteeism. Using data from Britain's Workplace Employee Relations Survey 2011, we show that the effects on stress-based absence are limited and not as predicted, but the effects on withdrawal-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 98 publications
(125 reference statements)
0
12
0
Order By: Relevance
“…One implication of these findings might be that managers should re‐think downsizing as a measure to improve organizations' profitability. However, this might not always be feasible, as the decision to downsize may depend on multiple factors (Datta et al, 2010), or be a recessionary action (Wood et al, 2020). Thus, organizations should try to prevent or reduce increases in job demands for surviving employees.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One implication of these findings might be that managers should re‐think downsizing as a measure to improve organizations' profitability. However, this might not always be feasible, as the decision to downsize may depend on multiple factors (Datta et al, 2010), or be a recessionary action (Wood et al, 2020). Thus, organizations should try to prevent or reduce increases in job demands for surviving employees.…”
Section: Discussionmentioning
confidence: 99%
“…We focus on downsizing consequences for those employees who remain in the organization (i.e., downsizing survivors). Downsizing is regarded as a stressor by surviving employees (Devine et al, 2003;Sonnentag & Frese, 2003) and has been positioned in the context of recessions in previous studies (Snorradóttir et al, 2013;Wood, Michaelides, & Ogbonnaya, 2020). However, it is not necessarily a consequence of decreased demand for organizations' products or services, as "proactive" downsizing may also occur during periods of healthy demand with the intention of enhancing long-term competitiveness (Datta & Basuil, 2015).…”
Section: Downsizing Consequencesmentioning
confidence: 99%
See 1 more Smart Citation
“…We therefore expect job insecurity to have affected well-being in the lockdown [ 36 , 37 , 38 ]. It is in our terms a COVID-19-related factor as the actions taken to mitigate it depressed demand in the economy and employees feared that employers would begin to lay-off employees or use other recessionary actions, which have been shown to increase job insecurity and decrease well-being [ 39 ]. We thus hypothesize that:…”
Section: Theoretical Focus and Hypothesized Relationshipsmentioning
confidence: 99%
“…3 Some of those studies are essentially descriptive in nature, while others attempt to identify the main factors associated with absenteeism, using either individual-level data or organizational-level studies. [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] Although absence definitions varied, a typological framework could be established using the following classifications of absence: voluntary or involuntary, planned, or unplanned albeit that some authors differentiate involuntary absenteeism (e.g., certified sickness) and voluntary absenteeism (e.g., annual leave or vacation, uncertified sickness). It has been further suggested that unplanned absence is often short-term and sometimes voluntary.…”
Section: Introductionmentioning
confidence: 99%